KRITERIA PENENTUAN TEORI PERTANGGUNGJAWABAN PIDANA KORPORASI OLEH HAKIM DALAM MEMUTUS TINDAK PIDANA KORPORASI - Putri Trie Lestari (2023)
This research was conducted to examine the theory of corporate criminal responsibility in Indonesia today and to relate it to judges' decisions in determining the theory of corporate criminal responsibility to be used. The background of this research is the regulation of corporate criminal liability in Indonesia, namely PERMA Number 13 of 2016 concerning Procedures for handling criminal cases by corporations by linking 3 (three) corporate criminal decisions using the theory of corporate criminal responsibility. This study uses a normative juridical approach. The results of the study show that corporate criminal responsibility in Indonesia has been regulated in each special criminal act law outside the Criminal Code. However, since the birth of the new Indonesian product Criminal Code, corporate criminal liability has begun to be regulated in detail, although it is still valid 3 (three) years after it was ratified. Regulated in each of the different laws makes the criminal responsibility different. This results in the absence of a unified regulation regarding corporate criminal liability. 3 (three) corporate criminal decisions The defendant is a corporation or individual who holds a position in a corporation and is responsible to the corporation using 3 (three) different theories. Judges who try corporate criminal cases are always of the opinion that the director's role is very vital in the running of the company, as long as he is not a director or a representative or an order from the director, then the company's criminal liability will be imposed individually, but as long as the director's intervention is involved and it is for the benefit of the company, the company will also be subject to the law with provisions for punishment regulated in the applicable laws and regulations.